The relationship between maternal involvement and self-compassion in parents of children with special needs : Hubungan Keterlibatan Ibu dan Self-compassion pada Orangtua Anak Berkebutuhan Khusus - Mauna, Mauna; PrameswarI, Savira (Journal of Research and Measurement in Psychology: JPPP, 2019)
This study aims to look at the relationship between maternal involvement and self-compassion in parentsof children with special needs. Maternal involvement is defined as maternal involvement in aspects of allchild's life seen from two different domains, namely affective and behavior. Self-compassion is the abilityof someone who can give attention and kindness to themselves when facing difficulties in life.Researchers use quantitative methods with a psychological scale. Mother Involvement was measuredusing’s the Nurturance Mothering Scales & Mother Involvement Scale developed by Finley & Schwartz,and the self-compassion was measured by Self-compassion Scale developed by Neff. The sample usedwas 165 people. Sampling uses non probability sampling. Method of data analysis in testing multiplehypotheses using correlation techniques. The results showed a significant relationship between maternalinvolvement with self-compassion with a value of r = 0.041 <p = 0.05, and a significant relationshipbetween maternal involvement reported with self-compassion with a value of r = 0.022 <p = 0 .5. Theresults of the study of the involvement of the desired mother with self-compassion showed no significantrelationship, with a value of p> 0.05.